A narrative review of the measurement methods for biomechanical properties of plantar soft tissue in patients with diabetic foot - Yang, Xiong-gang; Peng, Zhi; Liu, Xiang; Liu, Xiao-liang; Lu, Sheng (Frontiers in Endocrinology, 2024)
This article provides an overview of the development history and advantages and disadvantages of measurement methods for soft tissue properties of the plantar foot.The measurement of soft tissue properties is essential for understanding the biomechanical characteristics and function of the foot, as well as for designing and evaluating orthotic devices and footwear. Various methods have been developed to measure the properties of plantar soft tissues, including ultrasound imaging, indentation testing, magnetic resonance elastography, and shear wave elastography.Each method has its own strengths and limitations, and choosing the most appropriate method depends on the specific research or clinical objectives. This review aims to assist researchers and clinicians in selecting the most suitable measurement method for their specific needs.